2020
DOI: 10.1101/2020.06.09.20126045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Worries and concerns among healthcare workers during the coronavirus 2019 pandemic: a web-based cross-sectional survey

Abstract: Background: Healthcare workers (HCWs) treating and caring for patients with emerging infectious diseases often experience psychological distress. However, the psychological impact and behavior change of the coronavirus disease 2019 (COVID-19) pandemic among HCWs are still unknown. This study aimed to investigate the worries and concerns of HCWs regarding the COVID-19 pandemic. Methods: In this cross-sectional survey, a web-based questionnaire was distributed among HCWs working in hospitals or clinics across J… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
4
23
0
Order By: Relevance
“…While worry may not be classified as a mental illness, it is of importance as it could be a precursor of more severe mental illness if not addressed ( 31 ). These findings are comparable to those of a Japanese study that showed that majority (78%) of the healthcare workers were seriously worried about COVID-19 and being infected was one of the leading concerns ( 32 ). The high frequency of worry in our setting is in keeping with a recent review that indicated that other than the main diagnostic categories of mental illness, many healthcare workers have various concerns regarding COVID-19 that increase their risk of experiencing psychological distress ( 33 ).…”
Section: Discussionsupporting
confidence: 83%
“…While worry may not be classified as a mental illness, it is of importance as it could be a precursor of more severe mental illness if not addressed ( 31 ). These findings are comparable to those of a Japanese study that showed that majority (78%) of the healthcare workers were seriously worried about COVID-19 and being infected was one of the leading concerns ( 32 ). The high frequency of worry in our setting is in keeping with a recent review that indicated that other than the main diagnostic categories of mental illness, many healthcare workers have various concerns regarding COVID-19 that increase their risk of experiencing psychological distress ( 33 ).…”
Section: Discussionsupporting
confidence: 83%
“…They also stated that issues such as ambiguity regarding “how to deal with patients when they were unwilling to be quarantined at the hospital or did not cooperate with medical measures because of panic or a lack of knowledge about the disease” and “shortage of protective equipment” were also contributing to poor mental health of medical staff ( 2020 ). A study by Sahashi et al on 4,386 HCPs in Japan also found that consequence of becoming infected, restricted social contact, and a shortage in personal protective equipment were the most frequent concerns ( 2019 ). While our study was not meant to discover the reasons for this phenomenon, several issues can be speculated to have resulted in this state of high burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, I found no evidence of risk compensation on the extensive margin (at least on one dimension, absenteeism). It is possible that this kind of response was limited by moral or ethical considerations (Sahashi et al, 2021) or perhaps by more prosaic considerations such as losing one's job.…”
Section: Discussionmentioning
confidence: 99%